ANALISIS EFEKTIVITAS PENGELOLAAN DANA ZAKAT DALAM MENINGKATKAN KEMAMPUAN MASYARAKAT BERTAHAN HIDUP PADA MASA PANDEMI COVID-19 (STUDI PADA BAZNAS PROVINSI SUMATERA UTARA) - Nurul Wafiq Azizah Nasution; Azhari Akmal Tarigan; Muhammad Syahbudi (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to find out how effective the management of zakat funds is in improving people's ability to survive during the Covid-19 pandemic, and the efforts made to increase the effectiveness of zakat fund management during the Covid-19 pandemic. The research methodology used is qualitative research. The data collection technique used the interview and documentation method, namely conducting direct interviews with staff at BAZNAS North Sumatra Province and several mustahik who received zakat during the Covid-19 pandemic, then documenting the data obtained. The results of this study can be concluded that the management of zakat funds in BAZNAS of North Sumatra Province during the Covid-19 pandemic can be said to be effective, especially in terms of distribution, many people find it difficult to meet their basic needs because they are affected by the Covid pandemic and feel helped by the distribution of zakat funds. BAZNAS, North Sumatra Province, is one of the zakat institutions that plays a role in overcoming Covid-19 through the distribution of zakat from various programs, namely the North Sumatra Care Program, Healthy North Sumatra Development, Smart North Sumatra Development, prosperous North Sumatra Development, Taqwa North Sumatra Development Program, and we take care of Kyai. But in terms of collection, it is still not optimal where the amount of zakat realization is still far from its great potential, this is because there are still many Muslim communities who do not have the awareness to pay zakat in BAZNAS, North Sumatra Province.